(NqZYK I METAFIZIKA (B/s - (NmAKSAPETQN(B, (NaLEKSANDR gAMLETOWI^(B.s; (NiNSTITUT FILOSOFII I PRAWA nan ras; (NnACIONALXNAQ AKADEMIQ NAUK rESPUBLIKI aRMENIQs ((NeREWAN (B:s (NnOQN tAPAN(B,s, 2002)
Summary, p. 296-299
(NlITERATURA(B, (NSTR(B.289-295s
Keywords: (NqZYKOZNANIEs; (NfILOSOFIQs